Malaria zoonoses. - Baird, J (2009)
The genus Plasmodium includes many species that naturally cause malaria among apes and monkeys. The 2004 discovery of people infected by Plasmodium knowlesi in Malaysian Borneo alerted to the potential for non-human species of plasmodia to cause human morbidity and mortality. Subsequent work revealed what appears to be a surprisingly high risk of infection and relatively severe disease, including among travelers to Southeast Asia. The biology and medicine of this zoonosis is reviewed here, along with an examination of the spectrum of Plasmodium species that may cause infection of humans.